Praktyczny aspekt optymalizacji i modelowania sieci w procesach dystrybucji : zagadnienia wybrane - Maternowska, Małgorzata (Practical Context of Network Optimization and Modelling in the Distribution Processes : Selected Problems, 2005)
This paper discuses first the shortcomings of typical network optimization projects, and then suggests a six-step approach that considers the strategic and practical context. This approach is to combine modelling tools and decision support tools with a "top-down" design approach that includes a detailed understanding of the company present and future business strategy and the practical implementation requirements that could impact the recommendation.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 248-252